A model for human-computer trust : contributions towards leveraging user engagement - Sousa, Sónia (2016)
Trusting is a rather complex phenomena and this complexity has been increasing with the pervasiveness of computing systems. In this virtual realms, Human-computer trust represents a key issue in today’s organizations, and it has a significative role in leveraging interactions and mediating interrelationships and auto-regulate knowledge sharing processes. This paper reports an research framework, which aims to facilitate the use of the acquired understanding of the role of trust in (A) Human Computer Interaction; and in (B) Computer mediated Interaction. Results situate the model as a key contribute for leveraging people’s interactions and their technological artefacts.